ASKING QUESTIONS – IMPROVING PRACTICE - Knoll, Susan; Leifso, Genelle (Operating Room Nurses Association of Canada Journal, 2009)
Are you translating existing research into your perioperative practice or finding that you have unanswered questions related to perioperative patient care? Chulay’s framework offers a detailed and understandable method for perioperative nurses without a research background to become involved in questioning, and thereby influencing, perioperative patient care.